1991
DOI: 10.1155/1992/928727
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of Neisseria Species in Communities with Different Rates of Meningococcal Disease

Abstract: A single clone,Neisseria meningitidisserogroup C (C:2a:P1.2), was isolated from seven patients during a cluster of cases of meningococcal disease in Ontario in 1989. To determine whether the clone was present in asymptomatic individuals in the same population, pharyngeal swabs were taken from 7% (644 of 9125) of residents who were vaccinated during the outbreak. Rates of isolation ofNeisseriaspecies were also compared to those in two other geographical areas which did not have an elevated incidence of meningoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
1
11
2
Order By: Relevance
“…Whereas carriage rates of serogroup C meningococci are significantly lower than for serogroup B or non-groupable meningococci, and typically less than 1% even in outbreaks, 12 14 17 our study found serogroup carriage rates of 3% by December. This level increases the risk of outbreaks.…”
Section: Discussioncontrasting
confidence: 56%
“…Whereas carriage rates of serogroup C meningococci are significantly lower than for serogroup B or non-groupable meningococci, and typically less than 1% even in outbreaks, 12 14 17 our study found serogroup carriage rates of 3% by December. This level increases the risk of outbreaks.…”
Section: Discussioncontrasting
confidence: 56%
“…The latter explanation may be more feasible, since Edwards et al (9) have shown that invasive group C meningococcal disease occurs primarily in persons who are newly infected with the organism. The short carriage period prior to infection is supported by the fact that ET 15 isolates could not be found in group C meningococcal carriers during the outbreak in Victoria County in 1989 (12).…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies of pharyngeal carriage during community outbreaks of clonal serogroup C disease have repeatedly demonstrated low rates of carriage of the implicated pathogenic strain. 10,21,[32][33][34][35] These findings suggest a plausible link between the jail system and serogroup C meningococcal disease in the community -namely, the transmission of a more virulent but rarely carried strain of N. meningitidis from the jail to the community by asymptomatic carriers released from jail.…”
Section: Discussionmentioning
confidence: 99%
“…Previously identified risk factors for meningococcal carriage include living in a household with a person with meningococcal disease or a carrier, 17,36,38 an age from 15 to 24 years, 26,33,[39][40][41][42] white race, 21,33 male sex, 29,39 household or institutional crowding, 10,34,43,44 active and passive exposure to tobacco smoke, 39,45,46 and a recent history of upper respiratory tract infection. 26,27 In our study, high rates of carriage among men released from jail and those returning to jail suggest that the jail itself, rather than the community from which the men came, played a dominant part in producing meningococcal carriage among incarcerated men.…”
Section: Discussionmentioning
confidence: 99%